IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KECAMATAN KURANJI KOTA PADANG - hidayat panuntun muslim; Fitri Eriyanti; Adil Mubarak (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
his study aims to describe how the implementation of the Non-Cash Food Assistance (BPNT) program in Kuranji Sub-District, Padang City. The background of the problem in this study is that based on preliminary observations, BPNT is assistance provided by the government to alleviate poverty and prosper the families of beneficiaries of the assistance. The large number of people who do not understand and appreciate the government's commitment has made this program not running well. The type and data analysis uses a descriptive qualitative approach. Data sources consist of primary data in the form of a direct interview process and secondary data is data collected from the institutional literature related to this research. The technique of collecting data uses observation, interviews and documentation. Test the validity of the data using the data source triangulation technique. And data collection techniques with data reduction techniques, data presentation and conclusion drawing. The results of this study indicate that the implementation of the BPN program has not gone well because there are obstacles in the lower level government that have not optimized the BPN implementation smoothly. Many people do not know the process and there are still many underprivileged people who are not registered to receive the assistance.